2011
DOI: 10.1111/j.1365-2214.2011.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting children with neurodevelopmental disorders and/or behaviour problems

Abstract: Parenting children with multiple health conditions can be associated with less positive, less consistent and more ineffective parenting behaviours. Understanding the factors that are associated with the challenges of caring for these children may require additional research attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…Furthermore, research has demonstrated that parents of children with DD often show increased levels of irritation and decreased levels of tolerance related to their child's functioning and behavior to the extent that they tend to experience an inability to effectively cope with disruptive behaviors (Crnic et al 2005). As such, parenting can become more coercive, intrusive, and less positive overall, which may ultimately lead to increased incidence of behavior problems in children Crnic et al 2005;Deater-Deckard and Scarr 1996;Garner et al 2013;Hastings 2002;Jackson 2000). The findings evidenced herein support the mechanistic effect parent-child relational frustration plays in the association between parental distress and child behavior problems.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, research has demonstrated that parents of children with DD often show increased levels of irritation and decreased levels of tolerance related to their child's functioning and behavior to the extent that they tend to experience an inability to effectively cope with disruptive behaviors (Crnic et al 2005). As such, parenting can become more coercive, intrusive, and less positive overall, which may ultimately lead to increased incidence of behavior problems in children Crnic et al 2005;Deater-Deckard and Scarr 1996;Garner et al 2013;Hastings 2002;Jackson 2000). The findings evidenced herein support the mechanistic effect parent-child relational frustration plays in the association between parental distress and child behavior problems.…”
Section: Discussionsupporting
confidence: 56%
“…A range of additional child outcomes including adaptive behavior, emotion regulation, social skills and competence, and overall developmental progress may be important outcomes responsive to changes in parenting stress and parentchild relational frustration, and as such should be given appropriate attention in future investigations Crnic et al 2005;Feng et al 2008;Garner et al 2013;Hastings 2002;Lewallen and Neece 2015;Trentacosta et al 2008). Finally, the current study relied upon parent report given our study emphasis on parents' subjective experiences and evidence that modification in parent perceptions may be sufficiently powerful to incite clinically meaningful change in parent-child interaction (Korja et al 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Caring for a child with a neurodevelopmental condition is a particularly challenging parenting situation, because the increased levels of caregiving stress may exert negative effects on parents' and their children's adaptation outcomes (Garner et al, 2011; Peer, 2011). Given the fact that coping strategies can facilitate or hinder positive family adaptation to caregiving stress (Lin, 2000), the examination of parents' coping behaviors, such as behavioral disengagement, may be useful to improve our understanding of modifiable variables linking parent-child stressors and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although increased sorrow and stress does not characterise all families of a child with a disability, caregivers of children with CP are reported to experience symptoms of chronic sorrow that persists as children mature (Whittingham, Wee, Sanders, & Boyd, 2013) and greater levels of anxiety and depression (Barlow, Cullen-Powell, & Cheshire, 2006) than caregivers of typically developing children. These parenting challenges may negatively impact family processes, in particular parenting behaviours (Garner et al, 2011). Caregivers of children with neurodevelopmental disorders and/or externalising behaviour problems are reported to demonstrate less effective parenting behaviours (including less positive interactions and less consistency) than parents of typically developing children (Garner et al, 2011).…”
Section: Mastery Motivation and The Family Environmentmentioning
confidence: 99%
“…These parenting challenges may negatively impact family processes, in particular parenting behaviours (Garner et al, 2011). Caregivers of children with neurodevelopmental disorders and/or externalising behaviour problems are reported to demonstrate less effective parenting behaviours (including less positive interactions and less consistency) than parents of typically developing children (Garner et al, 2011). Considering children with CP are more likely to demonstrate externalising behavioural and emotional problems than typically developing peers (Carlsson, Olsson, Hagberg, & Beckung, 2008), it is reasonable to assume caregivers of children with CP will experience greater parenting challenges and engage in less effective parenting behaviours than caregivers of children without a disability.…”
Section: Mastery Motivation and The Family Environmentmentioning
confidence: 99%